3D-Printed electrodes for membraneless water electrolysis. Issue 1 (7th November 2019) - Bui, Justin C.; Davis, Jonathan T.; Esposito, Daniel V.
Abstract : This work describes a membraneless electrolyzer in which all key components are fabricated by 3D-printing processes. Abstract : Additive manufacturing encompasses an emerging class of techniques that are increasingly finding applications in the field of electrochemistry. While most of these demonstrations have involved the use of 3D-printing to fabricate structural components of electrochemical devices, this manuscript describes the design, manufacture and performance of 3D-printed porous flow-through electrodes employed in an electrolyzer that is itself made almost entirely by 3D-printing. These electrodes were 3D-printed using fused deposition modeling (FDM) from a composite of conductive carbon and polylactic acid (PLA), followed by electrodeposition of nickel (Ni) electrocatalyst. The stability and performance of these Ni-PLA electrodes were evaluated for water electrolysis in 1.0 M sodium hydroxide (NaOH). After characterizing the performance of a single electrode pair for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), three pairs of electrodes were incorporated into a simple and scalable 3D-printed membraneless electrolyzer by "clicking" them into a monolithic lid containing manifolding for collection of the O2 and H2 product gases. The device utilizes a membraneless architecture capable of operating in a stagnant electrolyte through buoyancy-driven separation of product gases, and allowing for easy regeneration of electrodes by electrodeposition. Device operation was evaluated through a combination of electroanalytical measurements, in situ high-speed video imaging, and finite element modeling. Although the efficiency and cross-over rates of these membraneless electrolyzers fall below what is required for commercial applications, additive manufacturing of electrodes offers an exciting new design space to improve performance and enable robust operation for applications where membrane-based electrolyzers are inherently unstable.